Hubungan Asupan Makan dan Kebugaran Fisik dengan Anemia pada Mahasiswi Gizi Universitas Negeri Surabaya, Indonesia: Dietary Intakes and Physical Fitness in Relation to Anaemia among Female Students Studying Nutrition at Universitas Negeri Surabaya, Indonesia - Sholihah, Lini Anisfatus; Rohmah, Noor; Syamsudi, Nur Anindya (Amerta Nutrition, 2025)
Background: Anaemia affects approximately 31.2% of Indonesian women of reproductive age and has been linked to inadequate dietary intake and lifestyle behaviours. Objectives: The present study aimed to determine the proportion of anaemia among female undergraduates in the Nutrition programme and to investigate its associations with dietary intake, anthropometric measures and physical activity levels. Methods: In this cross‐sectional study, 113 first- and second-year female Nutrition students completed three non-consecutive 24-hour food records to estimate daily intakes of energy, iron, folate, vitamin B₁₂ and vitamin C. Dietary diversity was quantified using the Dietary Diversity Score (DDS). Physical fitness was assessed via the Harvard Step Test, and anthropometric measurements body mass index, mid-upper arm circumference and body-fat percentage were recorded. Capillary haemoglobin concentrations determined anaemia status. Independent t-tests or Mann-Whitney U tests compared anaemic and non-anaemic groups, and logistic regression models estimated odds ratios for associations with anaemia. Results: 39% of participants were classified as anaemic. Fitness scores differed significantly between groups (anaemic: 43.7±2.1 vs non-anaemic: 51.4±2.5; p-value=0.03). In unadjusted analyses, higher folate intake corresponded to reduced odds of anaemia (p-value=0.02), but the association was no longer significant after adjustment for covariates. Conclusions: A high proportion of female Nutrition undergraduates remain anaemic. Public health initiatives should promote diets rich in iron and folate, encourage greater dietary diversity, and support regular physical activity to mitigate anaemia risk. Further research should evaluate targeted nutritional interventions and fitness programmes for this demographic.